Prediction of pKa values of pharmaceutical substances using quantitative structure-property relationship /cNur Ain Amirah Mansor - Nur Ain Amirah Mansor, 1990-; Mohamed Noor Hasan; msa 030611 (2011)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011